Bufei Jiedu Formula enhances CD40 activation and macrophage polarization to eliminate intracellular MRSA persisters - Zhang, Shaoyan; Chen, Jiajun; Qiu, Lei; Wu, Xianwei; Zhou, Wei; Peng, Ruoqing; Feng, Ya; Zhou, Rui; Huang, Xing; Wu, Dingzhong; Lu, Zhenhui (Frontiers in Immunology, 2025)
BackgroundIntracellular methicillin-resistant Staphylococcus aureus (MRSA) represents a complex infection in clinical practice, characterized by its refractory and recurrent nature, rendering it challenging to treat with conventional antibiotics. Bufei Jiedu Formula (BFJD) is a traditional Chinese medicine compound utilized for treating chronic lung infections; however, its mechanisms against intracellular MRSA infection are not yet fully understood.MethodsAn animal model with persistent MRSA infection was used to evaluate the efficacy of BFJD against chronic bacterial infections. Flow cytometry was employed to assess the regulatory effects of BFJD on macrophages. Transcriptomic sequencing and molecular biological experiments were utilized to explore and validate the regulatory targets and pathways of BFJD. Flow cytometry and molecular docking were used to clarify the possible binding mode of bioactive compounds with CD40.ResultsBFJD reduced bacterial loads in the lungs, liver, and kidneys of mice with persistent MRSA infection and promoted M1 polarization of macrophages in the lungs. In vitro, BFJD decreased intracellular MRSA persisters loads and enhanced macrophage M1 polarization and M2-to-M1 repolarization. Multi-time point cellular sequencing data revealed the transcriptomic characteristics of intracellular persistent MRSA infections, including the downregulation of cytokine activity and TNF signaling pathways. GO-KEGG enrichment analysis revealed that BFJD regulated signaling pathways related to response to reactive oxygen species (ROS), IL-1β and IL-6 production, NF-κB and TNF signaling. Further intersection analysis found that genes down-regulated in the persistence state were up-regulated by BFJD, among which pro-inflammatory genes including Il1b, Il6, Ccl2, and Cd40 were all reversed. Furthermore, we found BFJD enhanced the host-mediated intracellular killing of MRSA by macrophages via the CD40-ROS-NF-κB signaling cascade. Multiplex cytokine analysis showed that BFJD increased the levels of IL-1β, CCL-2, IL-6, and TNF-α in the serum of persistently infected mice. Further screening of active compounds revealed that atractylenolide II and formononetin exhibit high affinity with CD40 and decreased intracellular bacterial loads.ConclusionBFJD decreased organ bacterial loads in mice with persistent MRSA infection by regulating the CD40-ROS-NF-κB signaling pathway, thereby modulating macrophage immunophenotypes and exerting anti-MRSA persister effects.